`y= x^3 -x^2 -14x + 24 `

Let x= 2 ==> 8-4 -28 +24 = 0

Then (x-2) is a factor of y.

Now we will divide y by (x-2).

`x^2+x -12`

-----------------------

`x-2` `x^3 -x^2 -14x +24`

`x^3 -2x^2`

-------------------------

`x^2 -14x + 24`

`x^2 -2x `

---------------------

`-12x + 24`

`-12x + 24 `

`==> y= (x-2)(x^2+x-12)`

Now we will factor the quadratic equation.

`==> y= (x-2)(x+4)(x-3) `

Then, the zeros are:

**x= { 2, 3, -4}**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now